Analysis Protecting The Health Workers from the Transmission of Tuberculosis at Teaching Hospital: A Review of Policy and Practice - Alfiyyah, Arifah; Modjo, Robiana; Bachtiar, Adang (Journal of Indonesian Health Policy and Administration, 2024)
The Tuberculosis (TB) remains a significant threat, especially to healthcare workers exposed by the infected patients in hospitals. Hospital staff with latent TB are at risk of developing active TB. To mitigate this risk, enhancing hospitals through infection prevention and control (IPC) measures is essential. This study aimed to identify policies and practices related to TB prevention, particularly in a teaching hospital where healthcare workers, including medical students, need protection. The research was conducted at a teaching hospital in Depok, West Java, from January to February 2024. The research took place at a teaching hospital in Depok, West Java, from January to February 2024. A qualitative method was used, including in-depth interviews with hospital committee members, nurses, and administrative staff to gather insights, along with policy analysis regarding TB. In the Indonesian hospital TB health services, the regulation of occupational health regarding TB protection for hospital workers state from constitution law, presidential regulation, ministry of health and ministry of Manpower. However, the findings revealed that there are no policies specifically addressing TB to protect the workers in the hospital. Challenges such as financing TB screenings and raising healthcare workers' awareness of TB were highlighted as crucial factors. The study emphasizes the importance of improving risk management strategies and IPC to safeguard healthcare workers, recommending specific regulations for hospitals with national policy. These results highlight the urgent need for specific TB prevention policies, particularly from the government, to ensure implementation across all hospitals.